Production and characterization of boron carbide and silicon carbide reinforced copper‐nickel composites by powder metallurgy method - Akkaş, M. (Wiley, 2021)
AbstractIn this study, composite samples were produced by reinforcing boron carbide and silicon carbide particles in different rates by weight into copper‐nickel powder mixture using powder metallurgy method. The prepared powder mixtures were cold pressed under 600 MPa pressure and pelletized. The pelletized samples were then sintered in an atmosphere‐controlled furnace. Scanning electron microscopy to determine the microstructure of the produced samples and x‐ray diffraction method analysis to determine the phases forming in the structure of the produced samples were used and microhardness was taken to determine the effect of boron carbide and silicon carbide on hardness. In addition to that, the mechanical properties the transverse rupture strength were investigated using three‐point bending tests. The corrosion tests were performed potentiodynamic polarization curves of the samples in 3.5 % sodium chloride solution. The highest hardness value was measured as 162 HV 0.05 in the sample reinforced with 10 % boron carbide. As the amount of silicon carbide increased, the corrosion resistance of the composite increased. Moreover, as the amount of boron carbide increased, the corrosion resistance of the composite decreased. Load‐contact depth values were examined, copper‐nickel+10 % silicon carbide has the highest peak depth of 48.12.